Protective effect of essential oils on the shelf life of smoked and vacuum packed rainbow trout (Oncorhynchus mykiss W.1792) fillets - Coban, Ozlem Emir; Patir, Bahri; Yilmaz, Okkes (Springer India, 2014)
This study was investigated the effects of some oils on chemical, microbiological and sensory quality in vacuum packed smoked rainbow trout (Oncorhynchus mykiss W.1792) fillets. Acceptability scores for appearance, taste and odour of untreated and treated smoked trout decreased with storage time. The limit of sensory acceptance was reached after 56 days for the untreated samples, after 84 days for with rosemary and thyme oil-treated samples after 98 days for with sage oil-treated and after 112 days for with clove oil-treated samples. Significant differences were not found between groups as microbiological (p > 0.05). However, significant differences were found both among groups and during the storage in term of TBA (thiobarbituric acid) and PV (peroxide value), FFA (free fatty acid) values (p < 0.05). Essential oils as natural antioxidant can be used in conjunction with vacuum packed to enhance hot smoked fish quality.
Keywords: Essential oils; Smoked fish; Oncorhynchus mykiss; Shelf-life; Antioxidant activity